The Intercultural Education in Guatemala of the 21st Century: a critical regard from the history (2020)
The main objective of this article is to provide an explanation to the facing that intercultural education has in Guatemala. Its relevance is that it constitutes a questioning of educational practices and policies that have been normalized without the participation or intervention of historians. The method used is critical analysis, the methodology being a criticism that aims at establishing a balance between globalizing aspirations and the substitution of traditional education for the one that incorporates teaching in indigenous languages. The strategies studied have been those of a critical analysis, compiling evidence and testimonies of educational practices. Finally, it has been concluded that the understanding of intercultural education obeys an institutional vision that relates it to the solution of the educational problems of the indigenous population through the use of native languages and the rescue of cultural features of the original communities.